Tinjauan Prosedural Perlindungan Hukum Bagi Wajib Pajak Dalam Keberatan Bea Perolehan Hak Atas Tanah Dan Bangunan - Danendra Aryasatya Maheswara; Fatih Henning Octavian Haq; Yusrul Hana; Aprila Niravita; Muhammad Adymas Hikal Fikri; Harry Nugroho (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This article examines the procedural review of legal protection for taxpayers in filing objections to the Land and Building Rights Acquisition Duty (BPHTB). Legal protection for taxpayers is essential to ensure administrative justice and provide a guarantee of rights for those who dispute the BPHTB value determined by the authorities. This study highlights the stages of the objection procedure, the rights and obligations of taxpayers, and the role of the tax court in dispute resolution. Using a normative juridical approach, the article identifies shortcomings in the procedural system that may hinder access to justice for taxpayers. The findings reveal that a more transparent procedure and robust protection mechanisms are essential to safeguard taxpayers' rights in BPHTB dispute resolution.